2008
DOI: 10.1021/ja806860w
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Ligand Exchange: Detection of a Pentacoordinate Ru(II) Intermediate and Product Formation

Abstract: The ultrafast kinetics of ligand exchange of cis-[Ru(bpy)(2)(CH(3)CN)(2)](2+) were measured in H(2)O and CH(3)CN. The formation of the (3)MLCT excited-state and a five-coordinate intermediate are observed in both solvents within 2 ps after excitation (310 nm, fwhm approximately 300 fs). The (3)MLCT excited-state undergoes vibrational cooling (5-6 ps), then decays to regenerate the ground-state with a lifetime of approximately 50 ps. In CH(3)CN, ligand recombination takes place in 28 ps, while the formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
126
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(147 citation statements)
references
References 12 publications
16
126
1
1
Order By: Relevance
“…The differences in photoinduced ligand exchange among 1−3 are illustrated in Figure S12 (Supporting Information), which shows that the substitution of the two CH 3 CN ligands in 2 and 3 is complete in 5−60 min. In contrast, the photosubsitution of one CH 3 CN ligand for CD 3 41 It is evident in Figure 3 that irradiation of complex 1 in H 2 O for 20 min (λ irr ≥ 550 nm) results in a well-defined absorption peak with a maximum at 518 nm, attributed to the monoaqua intermediate 4, with negligible spectral changes with continued irradiation with this wavelength. However, when 4 is further irradiated with higher energy light (λ irr ≥ 420 nm), the bis-aqua species, 5, is formed after 3 h ( Figure S14 In contrast to the results described with respect to 1, irradiation of 2 (λ irr ≥ 455 nm, Figure 4a) and 3 (λ irr ≥ 610 nm, Figure 4b) results in complete conversion to the corresponding bis-aqua species.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The differences in photoinduced ligand exchange among 1−3 are illustrated in Figure S12 (Supporting Information), which shows that the substitution of the two CH 3 CN ligands in 2 and 3 is complete in 5−60 min. In contrast, the photosubsitution of one CH 3 CN ligand for CD 3 41 It is evident in Figure 3 that irradiation of complex 1 in H 2 O for 20 min (λ irr ≥ 550 nm) results in a well-defined absorption peak with a maximum at 518 nm, attributed to the monoaqua intermediate 4, with negligible spectral changes with continued irradiation with this wavelength. However, when 4 is further irradiated with higher energy light (λ irr ≥ 420 nm), the bis-aqua species, 5, is formed after 3 h ( Figure S14 In contrast to the results described with respect to 1, irradiation of 2 (λ irr ≥ 455 nm, Figure 4a) and 3 (λ irr ≥ 610 nm, Figure 4b) results in complete conversion to the corresponding bis-aqua species.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…40,41 It was shown that ligand exchange occurred in a stepwise manner and that the quantum yield for the exchange of the second CH 3 CN ligand is ∼2-fold lower than that of the first CH 3 CN ligand. 40,41 Moreover, in [Ru(bpy)(CH 3 CN) 4 ] 2+ , which possesses four potential sites for exchange, only the axial CH 3 CN ligands undergo stepwise substitution with water upon irradiation. 40 This reactivity provides an important synthetic tool for the preparation of new trans Tris−heteroleptic Ru(II) complexes, as well as PCT agents with photolablile ligands that can function in hypoxic environments without the need for oxygen.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The 1 MLCT absorption maxima of 3 and 4 are red-shifted compared to the analogous CH 3 CN complexes, as is well-known for other cis -Ru(II) complexes coordinated by two CH 3 CN and py ligands. 37,90 The quinoline moiety in 4 leads to a further red shift as compared to 3 . Again, the intensities of these transitions are in good agreement with those of [Ru(TPA)(py) 2 ] 2+ 57.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, with the exception of [Ru(bpy) 3 ] 2+ , [39][40][41] a fundamental understanding of the ultrafast excited state processes of transition metal complexes is still lacking.…”
Section: Introductionmentioning
confidence: 99%